Optical Solitons Solutions in Birefringent Fibers with Perturbed Generalized Gerdjikov–Ivanov Model using the Addendum to Sub-ODE Method - Zayed, Elsayed ME; Elghany, Alaa Abd; Shater, Mona El- (Annals of Mathematics and Physics, 2025)
For the perturbed generalized Gerdjikov-Ivanov (GI) model in polarization-preserving fibers, we study the propagation properties of optical solitons in birefringent fibers. A complementary and effective integration method, namely an addendum to the Sub-ODE method, is used to analytically handle the coupled (GI) equations once they have been reduced to tractable forms via the use of an appropriate similarity transformation. By using this method, a wide range of accurate closed-form solutions may be created, such as bright, dark, kink-shaped, solitary, bell-shaped, straddled, Jacobi elliptic and Weierstrass elliptic doubly periodic waveforms. We carefully construct explicit parametric constraints regulating the existence of each class. The findings give important information for developing sophisticated nonlinear fibre-optic systems, engineering photonic crystal structures and enhancing the propagation control of ultrashort optical pulses in high-capacity communication networks, in addition to enhancing the analytical solution space of the (GI) model. OCIS: 060.2310; 060.4510; 060.5530; 190.3270; 190.4370.